Ultrasound Diagnosis of Osteophytic Impingement of the Popliteus Tendon After Total Knee Replacement. (24th February 2018) - Geannette, Christian; Sahr, Meghan; Mayman, David; Miller, Theodore T.
Abstract : We report our experience with 6 patients who had total knee replacements with lateral‐sided knee pain, referred for ultrasound (US) assessment and US‐guided injection. All cases showed an osteophyte within the popliteus sulcus of the lateral femoral condyle impinging on the adjacent tendon. Five of 6 patients reported improvement of symptoms immediately after US‐guided injection of an anesthetic and a steroid. Ultrasound has a unique role in the imaging of knee replacements because of its real‐time capabilities and absence of artifacts at the popliteus tendon origin.